(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The current study aimed to know the level of job performance of newly hired university professors, as well as to know the level of their professional competencies in light of training via the PED@TIC platform, in addition to revealing the possibility of predicting the professional competencies acquired via the PED@TIC platform through the job performance of the study sample members, as the descriptive correlational approach was relied upon. To achieve the study objectives, a questionnaire of the professional competencies of the university professor was constructed in light of training via the PED@TIC platform, and the questionnaire of job performance of the university professor by "Sghairi and Bouafia" (2020) was adopted. After confirming the validity of the two tools through their psychometric properties, they were applied to a sample consisting of (43) newly hired university professors at the University of Ouargla, March 2023 batch. The study reached the following results: The level of job performance and professional competencies acquired via the PED@TIC platform for newly hired university professors at the University of Ouarglais high. The quality standard and the time standard contribute to predicting the professional competencies acquired via the PED@TIC platform among the study sample members